Baking Freecumipo (Freedom, Culture, Ministry, Policy): E-Learning through Games of Al-Islam and Kemuhamamdiyahan - Elihami, Elihami (EduPsyCouns: Journal of Education, Psychology and Counseling, 2021)
The aim of this article is baking freecumipo (freedom, culture, ministry, policy):  E-Learning through games of Al-Islam and Kemuhamamdiyahan. The method of the research is qualitative method. This research captured children's, development in AlK Education in measuring cultural freedom integrated with government policies, cognitive being the prima donna in the era of independent campuses by having skills in industry as material mind set in the millennial era, so that the affective and personality aspects of Al-Islam and Kemuhammadiyahan are not maximized, the content of Al-Islam and Muhammadiyah material often occurs remedial due to lack of syncorization between Al-Islam and Kemuhammadiyahan institutions.